The Contribution of Shaykh Yasin Al-Fadani to the Dynamics of Hadith Scholarship in the Nusantara - Siti Fatihatul Hikmah; Ida Rochmawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Islamic intellectual history in the Nusantara has developed through transregional scholarly networks linking local communities with global centers of learning, especially the Haramain. Specific Background: Shaykh Yasin Al-Fadani, a Minangkabau-born scholar based in Mecca and known as Musnid ad-Dunya, held a central role in hadith transmission and Islamic astronomy, connecting the Haramain and the Nusantara through his works and students. Knowledge Gap: While prior studies address his hadith and astronomical contributions, limited analysis applies Karl Mannheim’s sociology of knowledge to explain his role in Nusantara intellectual dynamics. Aims: This study investigates how his social position, intellectual networks, and writings sustained Islamic scholarly continuity between the two regions. Results: Through qualitative case study and content analysis, the findings show that he preserved sanad authority, established extensive teacher–student networks, and authored key works such as Al-Fawaid Al-Janiyyah and Al-Mukhtasar Al-Muhazzab, which remain central in pesantren education and responsive to colonial and modern contexts. Novelty: By employing Mannheim’s framework, this research situates his scholarship within its socio-historical setting and transregional interactions. Implications: The study clarifies Nusantara–Haramain scholarly connectivity and reaffirms the ongoing relevance of sanad-based learning in contemporary Islamic education. Highlights: A transregional teacher–student lineage linked Mecca with pesantren communities across Java, Sumatra, and Kalimantan. Sanad-centered scholarship functioned as a mechanism for preserving religious authority during colonial and modern transitions. Major writings on hadith and Islamic astronomy addressed both doctrinal continuity and practical communal needs. Keywords: Syekh Yasin Al-Fadani, Nusantara, Islamic Intellectualism, Sociology of Knowledge